Peningkatan Pengetahuan Perawat tentang Keselamatan Pasien - Anggreini, Yunita Dwi; Kirana, Wahyu; Priyatnanto, Hendra (Universitas Malahayati, 2024)
ABSTRACT Implementing patient safety in hospitals is still a challenge that every hospital needs to face. Incidents may be found due to suboptimal implementation of patient safety targets which results in increased hospital days and increased treatment costs. The aim of this research is to analyze the effect of training on knowledge about patient safety. This research uses a quasi-experimental design. A total of 30 respondents were involved in this research who were chosen randomly. Respondents in this study were nurses with a nursing diploma and bachelor's degree in nursing and professional educational background. The results of the study showed that there was an effect of training on increasing nurses' knowledge about patient safety with a value of p= 0.02 (p<0.05). Nurses who have good knowledge and understanding of patient safety provide a sense of security for patients and families who are treated in hospital. Keywords: Knowledge, Training, Patient Safety ABSTRAK Penerapan keselamatan pasien di rumah sakit masih menjadi tantangan yang harus dihadapi setiap rumah sakit. Insiden dapat ditemukan akibat penerapan target keselamatan pasien yang belum optimal yang mengakibatkan bertambahnya hari rawat inap dan bertambahnya biaya perawatan. Tujuan penelitian ini adalah menganalisis pengaruh pelatihan terhadap pengetahuan tentang keselamatan pasien. Penelitian ini menggunakan desain quasi eksperimen. Sebanyak 30 responden dilibatkan dalam penelitian ini yang dipilih secara acak. Responden dalam penelitian ini adalah perawat dengan latar belakang pendidikan diploma keperawatan dan sarjana keperawatan serta profesi. Hasil penelitian menunjukkan bahwa ada pengaruh pelatihan terhadap peningkatan pengetahuan perawat tentang keselamatan pasien dengan nilai p= 0,02 (p<0,05). Perawat yang memiliki pengetahuan dan pemahaman yang baik tentang keselamatan pasien memberikan rasa aman bagi pasien dan keluarga yang dirawat di rumah sakit. Kata Kunci: Pengetahuan, Pelatihan, Keselamatan Pasien